2016
DOI: 10.1007/s12272-016-0846-1
|View full text |Cite
|
Sign up to set email alerts
|

Moisturizing effect of serine-loaded solid lipid nanoparticles and polysaccharide-rich extract of root Phragmites communis incorporated in hydrogel bases

Abstract: This study evaluated the moisturizing effect of serine-loaded solid lipid nanoparticles (serine-SLN) and polysaccharide-rich reed (Phragmites communis) root extract (RRE) incorporated in hydrogel bases. The hydrogels with serine-SLN and/or RRE were carefully applied on the volar forearm of human volunteers. Their moisturizing efficacy was evaluated by monitoring conductance values using a skin surface hygrometer. The values of the area under the normalized conductance-time curve (AUCC) were developed and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The crude polysaccharides (TCSP and TCPP), and other common humectants in cosmetics (e.g., chitosan, sodium alginate and sodium hyaluronate) were selected. The samples were all oven-dried for 4 h at 100 °C and then placed in a sealed humidity chamber with a saturated Na 2 CO 3 solution (43% RH) and a saturated (NH 4 ) 2 SO 4 solution (81% RH) at 25 °C for the indicated time [ 57 , 58 ]. The moisture absorption ability (Ra) was measured as follows: where W 0 and W 1 are the sample weights before and after being put into the chamber, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The crude polysaccharides (TCSP and TCPP), and other common humectants in cosmetics (e.g., chitosan, sodium alginate and sodium hyaluronate) were selected. The samples were all oven-dried for 4 h at 100 °C and then placed in a sealed humidity chamber with a saturated Na 2 CO 3 solution (43% RH) and a saturated (NH 4 ) 2 SO 4 solution (81% RH) at 25 °C for the indicated time [ 57 , 58 ]. The moisture absorption ability (Ra) was measured as follows: where W 0 and W 1 are the sample weights before and after being put into the chamber, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Nanoformulation systems can be constructed based on inorganic materials (metallic nanoparticles) and organic materials (lipids and polymer nanoparticles) [308]. Nanoparticle carriers should be biocompatible and biodegradable [309,310]. It has been shown that carbon nanoparticles, metallic nanoparticles, and even solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC) may be potentially toxic [307] due to the small size or composition of the nanocarriers.…”
Section: Nanotechnology-based Carotenoid Delivery Systemsmentioning
confidence: 99%

Skin Protection by Carotenoid Pigments

Flieger,
Raszewska-Famielec,
Radzikowska-Büchner
et al. 2024
IJMS